The potential for tailored screening to reduce bowel cancer mortality for Aboriginal and Torres Strait Islander peoples in Australia: Modelling study. (June 2022) - Lew, Jie-Bin; Feletto, Eleonora; Worthington, Joachim; Roder, David; Canuto, Karla; Miller, Caroline; D'Onise, Katina; Canfell, Karen
Abstract: Background: Australian Aboriginal and Torres Strait Islander peoples experience health and socioeconomic disparities, including lower life-expectancy, have a younger mean age of colorectal cancer (CRC) diagnosis, and lower CRC survival than non-Indigenous Australians. The National Bowel Cancer Screening Program (NBCSP) provides biennial CRC screening for Australians aged 50–74 years to reduce the burden of CRC. The 2019 participation rate was 42% nationwide and 23% in Aboriginal and Torres Strait Islander peoples. For Aboriginal and Torres Strait Islander peoples, this study aims to estimate the health outcomes and cost-effectiveness of the current NBCSP and extensions to include people < 50 years. Methods: An existing microsimulation model, Policy1-Bowel, was adapted to the Aboriginal and Torres Strait Islander population and was used to evaluate three strategies assuming biennial iFOBT screening from 50-74, 45–74, or 40–74 years under two participation scenarios: 23% and 42% per screening round (psr.). Results: At 23–42% participation psr., the current NBCSP was predicted to reduce lifetime CRC incidence and mortality by 14–24% and 23–39%, respectively, be cost-effective (incremental cost-effectiveness ratio <$13, 000/life-year saved), and be associated with a benefits-and-burden balance of 51-53 number-needed-to-colonoscope (NNC) per CRC death prevented of . Lowering the screening start age to 40(45) would further reduce CRC incidence and CRC mortality by 7–11(4–5) percentage points, be cost-effective, and be associated with an incremental NNC- of > 95 (> 60). Conclusion: For Aboriginal and Torres Strait Islander peoples, the current NBCSP is cost-effective but participation is limited. Lowering the screening start age will further reduce CRC incidence and mortality. Policy summary: These findings highlight a need to increase NBCSP participation whilst exploring the feasibility and acceptability of lowering the NBCSP start age for Aboriginal and Torres Strait Islander peoples. These findings could inform new co-designed, community-led strategies to improve CRC outcomes for Aboriginal and Torres Strait Islander peoples. Highlights: This is the first NBCSP evaluation for Aboriginal and Torres Strait Islander peoples in Australia. The current NBCSP is cost-effective and can reduce CRC deaths. Increasing NBCSP participation can save more lives. Extending NBCSP to 40–49 years is cost-effective and can save more lives.